IS IMPULSE BUYING COULD BE MANAGED: LESSON FROM ALFAMART INDONESIA? - WAWAN NOVIANTO; JOHANNES JOHANNES; SYAHMARDI YACOB (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
Impulse buying is mportant to be managed particularly on retail competitive marketing practice. The research purpose is to analyze the influence of store atmosphere, sales promotion on impulse buying where positive emotion is treated as mediation factor. To establish that purpose, survey is conducted where the unit analysis is Alfamart’s customer. Sample is chosen in quota way as many as 100 customers. The analytical method used is Partial Least Square (PLS). The results showed that store atmosphere has an effect on positive emotion, sales promotion influence positive emotion, and positive emotion influence impulse buying. Store atmosphere and sales promotion also indirectly affect impulse buying where the mediation factor is positive emotion. In practice, sales promotion is well conducted by the employee which created employee-customer relation and emotion as well. Hence, in order to sustain impulse buying practice, store atmosphere should be managed in an interesting way as well as sales promotion. Sales promotion however has important role, where the role of the employee is not only manage transaction, but encouraging consumer to buy more through their own emotion. In doing so, employee should be encouraged, pushed to manage sales promotion in order to sustain impulse buying. Hence future research relate with the role of technology and employee as the basis of retailer to build competitiveness over their competitors.